PENERAPAN PROGRAM LINIER PADA PERMAINAN NON-KOOPERATIF - Pardi Affandi (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2011)
This paper will examine the application of linear programming to the game non-cooperative. It starts with the application of a linear program on the game of point of view of player I. In the same way players II problems can be brought into the form of a linear program. The equation obtained is the form dual program, the same result will be obtained that is the maximum result gained player I equal to the minimum result that players sought II against player I. Furthermore the game will be solved by the pivot method, so that the strategy and results obtained from the game.